THE CONTEXTUAL USE OF FAMILY UPBRINGING TERMINOLOGY IN ENGLISH AND UZBEK LITERARY PEDAGOGICAL AND PUBLICISTIC TEXTS - Sarvinoz Rashidova Ilhom qizi (Modern American Journals, 2025)
This article explores the contextual and pragmatic use of family upbringing terminology in English and Uzbek literary, pedagogical, and publicistic texts. The study aims to identify how these terms reflect cultural values, communicative intentions, and moral concepts across two linguocultural traditions. Through comparative linguistic and discourse analysis, the research demonstrates that while English family-related terms emphasize individuality, independence, and personal responsibility, Uzbek equivalents prioritize collectivism, respect, and moral upbringing. The results show that the contextual meanings of family upbringing terms reveal not only linguistic but also deep cultural and value-based divergences.
Keywords: Family upbringing, terminology, pragmatics, discourse, context, English, Uzbek, comparative linguistics.